Application of bilateral sliding mode predictive compound control in photoelectric tracking system. (June 2023) - Yan, Ren; Yimin, Wang
This article focuses on the stable imaging problem of photoelectric imaging system that depends on the synchronous rotation of mirror and detector. When there is a relative movement between the mirror and the detector, it will cause image rotation, resulting in information loss and reduced tracking accuracy. It is difficult to achieve the high-precision synchronous movement between the mirror and the detector using the traditional unilateral control method. Different from the existing results of the traditional unilateral tracking method, this paper introduces the bilateral control structure in the field of robot teleoperation and proposes a novel compound control strategy based on the bilateral control structure. First, a robust disturbance observer is proposed to reduce the disturbance of the system, in which a new robust H ∞ mixed sensitivity control algorithm is designed to optimize the filter. Then, a novel generalized sliding mode predictive (NSMP) control strategy based on hybrid reaching law is proposed to eliminate the image rotation problem caused by time delay. Besides, a new power function is designed to replace the switching function in the reaching law to reduce chattering. Finally, the finite time theory and the Lyapunov theory are used to prove that the proposed control scheme can ensure that the system is stable and reach its steady state in a finite time. The simulation results show the effectiveness of the proposed control scheme.